Revisiting knowledge on ESG/CSR and financial performance: A bibliometric and systematic review of moderating variables - Marcos Alexandre dos Reis Cardillo; Leonardo Fenando Cruz Basso (Journal of Innovation & Knowledge)
This study conducts a comprehensive bibliometric analysis and systematic review to investigate the moderating variables that influence the relationship between Environmental, Social, and Governance (ESG) measures, Corporate Social Responsibility (CSR) measures, and Corporate Financial Performance (CFP). Analyzing 108 articles from the Web of Science and Scopus databases published between 2019 and 2023, the study identifies key variables, influential studies, and methodological approaches within the ESG/CSR-CFP nexus. The findings reveal that moderating variables such as governance structures, cultural norms, technological readiness, market maturity, economic conditions, industry characteristics, firm strategy, and CSR engagement levels significantly impact the strength and direction of ESG and CSR effects on financial performance. However, the literature demonstrates considerable inconsistencies due to diverse research designs, varying definitions of ESG and CFP, and underrepresentation of moderating variables such as social and cultural factors, technological readiness, and firm-specific characteristics. The study highlights the need for more standardized variables, advanced research methodologies, and a broader exploration of these underexamined moderating variables to develop a more nuanced understanding of how ESG and CSR initiatives influence corporate financial outcomes. This work provides a framework for future research to address these gaps, enhancing the academic discourse on corporate sustainability and financial performance.